(untitled) (Comprehensive Journal of Science, 2026)
This study aims to develop practical solutions for the high salinity levels in the Quaternary aquifer in the northwestern Jafara Plain, which has reached 17,000 mg/L, by blending it with the higher-quality Miocene aquifer water (3,200 mg/L). The research utilized an experimental-analytical approach, conducting a series of laboratory blending experiments with gradual ratios, supported by a mathematical model based on the Mass Balance Equation. The results demonstrated that the blending process significantly reduced Total Dissolved Solids (TDS) and Electrical Conductivity (EC). The study concluded that a blending ratio of (0.5 : 9.5) —representing 5% from the Quaternary aquifer and 95% from the Miocene— is the optimal ratio that balances water quality improvement (reaching approximately 3,890 mg/L) with the sustainability of groundwater resources. The paper recommends implementing field engineering solutions, such as "Smart Mixing Units" and "Dual Completion Wells," to maximize the utilization of available water resources and reduce pressure on deep aquifers.